(untitled) (Mustansiria Dental Journal, 2024)
Thalassaemia is considered one of the major health problem, which is widely ,distributed throughout the world Clinical orofacial, and radiographical examinations, in addition to the physical and biochemical analysis of the whole unstimulated saliva had been studied in Major thalassaemia patients (MTP) and the results compared with that of the normal .subjects )The study included (254) subjects. Thalassaemia patients (study group composed of (201) patients and non-thalassaermic. patients (control group) composed of (53) subjects. Each group was divided into three subgroups according to their ages .and sex distribution to study the chronological changes ofthe disease The first,second, and third groups were (6-11, 12-17,2 18) years old .respectively The results of the study showed that, there was a significant difference in ,occlusal relation between thalassaemie and non·thalassaemic groups Thalassaemic patients had a significant degree of malocclusion and high .significant degree of teeth discoloration than non-thalassaemie patients There were significant difference in oral hygein indices between thalassaemie and non-thalassaemie patients and even between male and female thalassaemie .patients The intraoral radiographical assessment of the major thalassaemie patients showed that, there was thinning of the lamina dura and bone marrow hyperplasia .which were significant when compaired with the non-thalassaemie patients Facial pigmentation and saddle no se were highly significant in major .thalassaemie than non-thalassaemie patients